Thermoelastic analysis of pressurized hollow spherical vessels with arbitrary radial non-homogeneity - Rani, Pooja; Singh, Kuldip (Zielona Góra: Uniwersytet Zielonogórski)
In this study, a general analysis of one dimensional steady-state thermal stresses of a functionally graded hollow spherical vessel with spherical isotropy and spherically transversely isotropy is presented with material properties of arbitrary radial non-homogeneity. The material properties may arbitrarily vary as continuous or piecewise functions.
Keywords: functionally graded material; thermal stresses; radial non-homogeneity; pressure; spherical vessel